Protection of Whistleblowers in Election Crime - Ali, La Ode Bunga; Mansyah, Muh Sutri (Law Research Review Quarterly, 2018)
This article aims to find out and analyze the protection of whistleblowers or reporters in election crime, here the author uses a type of normative juridical research with the statutory approach, conceptual approach and case approach, this is motivated by elections held once every 5 years. It is undeniable that violations often occur before the election and when the election is held, according to Bawaslu that there are 3,133 cases of violations either in the form of findings or reports as referred to in the 2018 elections in 171 regions. So that in following up on election crime, there must be a role from whistleblowers from the public, but there is fear from the reporter so that he does not dare to report the crime, so protection against whistleblowers is needed. The election has not clearly stipulated in the form of protection given, one of the problems is that the reported party reports the reporter again so that the consequences are not continuing the case from investigation to incrach decision but only limited to the level of investigation caused by obstacles experienced is evidence that is owned by the complainant, then the whistleblower should be given protection such as having the right of immunity as cannot be prosecuted criminal or civil, protecting in order to avoid ri from economic, political and social discrimination.